Analisis Kompetensi Profesional Guru dalam Menerapkan Pembelajaran Tematik di Sekolah Dasar - Siswanto Siswanto; Supeno Supeno (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to describe the professional competence of teachers in implementing thematic learning in elementary schools. The research method used is descriptive qualitative research method, with preparation/pre-field steps, field work, and data analysis. The data sources who are the key people are all 8 teachers of SDN 010 Tambusai, consisting of 2 male teachers and 6 female teachers. The data collection technique used is the analysis of the teacher's professional competence and observation. The research instrument used was the teacher's professional analysis sheet and the teacher's thematic learning implementation observation sheet. The data analysis technique was carried out using qualitative data analysis techniques. The results showed that the professional competence of teachers viewed from educational background was at a good level. The professional competence of teachers in carrying out thematic learning is at a good level. The conclusion of this research is the professional competence of teachers in implementing thematic learning is at a good level. The local Education Office needs to pay attention to the distribution of teachers who teach at the elementary level. It is necessary to pay attention to the educational background so that the professional competence of teachers can be maintained and can be improved in the future. For teachers who already have a career in elementary schools, continuous training and assistance are needed in order to maintain and improve their professional competencies which can directly improve the competence of their students.